Teknik Menulis Jurnal untuk Meningkatkan Rasa Syukur (Gratitude) pada Remaja - Ima Ratnasari; Dewang Sulistiana (Journal of Innovative Counseling : Theory, Practice, and Research, 2020)
Various aspects that support the optimal process of adolescent development need to be considered, one of which is adolescent happiness and well-being. One of the variables that supports this is Gratitude. A descriptive study was conducted on 328 students of grade XI at SMAN 1 Manonjaya with a sample of 167 people to see a general picture of gratitude. The measuring instrument used is the development of the Gratitude Resentment and Appreciation Test (GRAT) designed by Watkins et al in 2003. The results showed that 149 students were in the high category or 89%, 15 students or 9% were in the medium category and 3 people students or 2% are in the low category. This shows the tendency of students to have the characteristics of grateful people that have felt abundant, respect for simple things and respect for others. Writing a Gratitude Journal has recommended previous studies with the assumption that if individuals write down the good they get every day, then the individual will focus on the good or positive rather than thinking about the negative.